Border restrictions during the pandemic COVID-19 in Latin America and the Caribbean - Gallegos, Miguel (2025)
Introduction: This study analyzed the effect of travel restrictions, including closure of borders and the cancellation of international flights in Latin America and the Caribbean, as one of the early measures implemented to control the spread of COVID-19 virus. Methodology: Literature review examining governmental and scientific databases as well as news-press publications. The material obtained was organized according to the dates of the first cases of COVID-19, notifications informing closure of borders, flights suspension, and travel rebound. The data was crosschecked with the reports of the passengers stranded in Latin American countries highlighting governments' roles in response to the pandemic. Results: Travel restrictions and border control measures affected several passengers returning to their country of origin and/or legal residence. Passengers experienced overwhelming challenges impacting their socioeconomic status, families, health, and employment. Discrimination was also a topic addressed. Many citizens of Latin American countries stranded in various Latin American regions were forced to restructure their travel plans and spend several months in places other than their homes. Conclusions: The early measures had several unintended consequences in the lives of countless individuals, despite their effectiveness in decreasing the transmission of the virus